Molecular epidemiology of Entamoeba Histolytica, Entamoeba Dispar and Entamoeba Moshkovskii infections in rural yemen / Mona Abdullah Mohammed Al-Areeqi - Mona , Abdullah Mohammed Al-Areeqi (2018)
Intestinal amoebiasis is highly prevalent in Yemen particularly in rural areas; however there is a great scarcity of information on the prevalence of species-specific Entamoeba infections in Yemen and many other countries due to the re-description of pathogenic Entamoeba histolytica and non-pathogenic E. dispar and E. moshkovskii. Therefore, this community-based study is the first to provide information on the true prevalence of E. histolytica, E. dispar and E. moshkovskii infections in rural communities in Yemen. The study also aimed to examine the association of these Entamoeba infections with some potential risk factors. A total of 605 stool samples from four provinces namely Sana’a, Dhamar, Taiz and Hodiedah were randomly collected and examined by wet mount, formalin-ether sedimentation, trichrome staining and nested multiplex PCR techniques. Demographic, socioeconomic and environmental information was collected by using a pre-tested questionnaire. Overall, 324 (53.6%) of the samples were positive for Entamoeba cysts and/or trophozoites by microscopic examination. The prevalence was significantly higher among male participants compared to female (P = 0.008). An agedependency distribution was also observed (P< 0.001). Using molecular analysis, it was found that 20.2%, 15.7% and 18.2% of the samples were positive for E. histolytica, E. dispar and E. moshkovskii, respectively. Multivariate analysis showed different sets of species-specific risk factors among these communities. Educational level was identified as the significant risk factor for E. histolytica; age and gender were the significant risk factors for E. moshkovskii; and sources of drinking water and consumption of unwashed vegetables were the significant risk factors for E. dispar. Moreover, living in coastal/foothill areas and presence of other infected family members were risk factors for both E. histolytica and E. moshkovskii infections. The present study provides new insight into the distribution and risk factors of intestinal amoebiasis in Yemen and reveals that Entamoeba spp. infection is highly prevalent among these communities iv with E. histolytica, E. dispar and E. moshkovskii differentiated for the first time.Hence, the study emphasizes the need for molecular methods in the diagnosis of infections and for conducting a large-scaled study throughout Yemen to determine the actual speciesspecific prevalence of Entamoeba spp. Moreover, identifying and treating infected family members, providing health education pertinent to good personal and food hygiene practices, and providing clean drinking water should be considered in developing a strategy to control intestinal parasitic infections in these communities, particularly in the coastal/foothill areas of the country